Dr. Marion Guillou on European food production, food security and climate change - Guillou, Marion (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Climate change is now being felt in all aspects of agriculture, from global commodities markets to the fields of French farmers. Is the link between food security and climate change widely accepted and is climate change affecting Europe's food production?